Verification of a mathematical model for wood joist floor systems - Goodman, J. R., author; Criswell, M. E., author; Bodig, J., author; Thompson, E. G., author; Vanderbilt, M. D., author; Liu, Jeong-Schwu, author; Civil Engineering Department, Colorado State University, publisher (Colorado State University. Libraries, 1974)
The primary objective of this study is to develop verification for the validity of a mathematical model for the behavior of wood joist floor systems under working loads. This complex, multi-layered structural system consists of joists acting in incomplete composite and two-way behavior with one or more layers of sheathing. This physical system is simulated by a crossing-beam model consisting of a perpendicular set of T-beams and sheathing strips in developing the mathematical model. To allow the use of ordinary beam theory in evaluating the behavior of the T-beam elements, the effective flange width of the incomplete composite sheathing elements was required. An essential part of this study was the derivation and quantification of the effective flange width for a wide variety of parameters. Two solution techniques are presented for the mathematical model, a finite difference method and a more versatile finite element procedure. Methods are developed to evaluate the effect of gaps in the sheathing layers and the results of the effective flange width study are utilized in the theoretical solutions. A total of twenty-two full-scale floor tests are conducted as part of an experimental program to provide the necessary data for verification of the mathematical model. Generally excellent agreement was obtained between the computed and the measured results. An average algebraic error of +3.24 percent was obtained for the computed results as compared to the measured deflection for the twenty-two specimens studied. As indicated, the predicted values from application of the mathematical model are generally conservative. The verified mathematical model was used to evaluate extreme cases to assess individual effects of composite and two-way action of wood joist floors. In addition, parameter studies were conducted to isolate the effects of major variables. The verified model provides the basis for future development of improved design criteria for wood joist structural systems.
CER74-75JSL-JRG-MEC-JB-EGT-MDV13.
August 1974.
Keywords: Floors, Wooden -- Mathematical models